Claims on Ready-to-Eat Cereals: Are Those With Claims Healthier? - Parra-Murillo, María; Lowery, Caitlin M.; Gómez, Luis F.; Mora-Plazas, Mercedes; Taillie, Lindsey Smith; Dillman Carpentier, Francesca R. (Frontiers in Nutrition, 2021)
Background: The use of advertising content strategies that suggest consuming a product will confer nutrient- and health-related benefits influences household food purchasing decisions, which increases consumption of energy-dense, nutrient-poor products. We examined the presence of marketing claims regarding nutrient content, health and nature in ready-to-eat (RTE) cereal packages in relation to the products' nutritional quality. Methods: A cross-sectional content analysis was conducted on 178 RTE cereal packages available in the six largest supermarket chains in four Colombian cities from August to November 2018. The nutritional quality of products was assessed through the nutrient profile model established by the Chilean Law of Food Labeling and Advertising law. Results: All products sampled exceeded the regulation threshold for at least one nutrient of concern (e.g., high-in calories and/or sugar). The majority (66.3%) of packages had claims related to nature, 57.3% had nutrient-content claims, and 15.7% had health benefit or risk avoidance claims. Most products with nature, nutrient-content, and health claims were high in energy (99.2, 98.0, and 92.9%, respectively) and sugar (88.1, 87.3, and 92.9%, respectively). Conclusion: RTE cereal products offered in major Colombian supermarket chains are heavily marketed using nutrition- and nature-related claims. Nearly all products with claims are high in energy and sugar, despite the messages conveyed by the claims to consumers. Results support the implementation of mandatory regulations restricting claims on food and beverage products high in nutrients of concern.